Thinking at the speed of bias how to shift our unconscious filters - Taylor, Sara (Berrett-Koehler Publishers, Inc., 2024)
"Founder of deepSEE Consulting shows how to understand and react consciously to cultural differences so we can catch unconscious biases and implement effective, transformational change"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Prejudices; Discrimination; Multiculturalism; Organizational change; Préjugés; Multiculturalisme; Changement organisationnel; multiculturalism